2013
DOI: 10.4161/hv.25735
|View full text |Cite
|
Sign up to set email alerts
|

Cross reactivity of serum antibody responses elicited by DNA vaccines expressing HA antigens from H1N1 subtype influenza vaccines in the past 30 years

Abstract: In the past three decades, ten H1 subtype influenza vaccines have been recommended for global seasonal flu vaccination. Some of them were used only for one year before being replaced by another H1 flu vaccine while others may be used for up to seven years. While the selection of a new seasonal flu vaccine was based on the escape of a new emerging virus that was not effectively protected by the existing flu formulation, there is limited information on the magnitude and breadth of cross reactivity among H1 subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…HA is the major protective antigen in clinically licensed inactivated and live-attenuated influenza vaccines. DNA vaccines expressing HA have been shown to be immunogenic in eliciting HA-specific antibodies in both animal and human studies (2,(30)(31)(32)(33)(34). The expression of HA antigen by pH1HA used in the current study was confirmed by Western blot and its immunogenicity to elicit HA-specific antibody response was verified in a pilot mouse study (data not shown).…”
Section: Dna Vaccine Plasmid Induces Expression Of Aim2 Caspase-1 Anmentioning
confidence: 57%
“…HA is the major protective antigen in clinically licensed inactivated and live-attenuated influenza vaccines. DNA vaccines expressing HA have been shown to be immunogenic in eliciting HA-specific antibodies in both animal and human studies (2,(30)(31)(32)(33)(34). The expression of HA antigen by pH1HA used in the current study was confirmed by Western blot and its immunogenicity to elicit HA-specific antibody response was verified in a pilot mouse study (data not shown).…”
Section: Dna Vaccine Plasmid Induces Expression Of Aim2 Caspase-1 Anmentioning
confidence: 57%
“…To confirm these results with a DNA vaccine expressing a viral immunogen, we vaccinated mice with DNA vaccine pH1HA expressing the HA antigen of the influenza A virus which was responsible for the H1N1 pandemic in 2009. As HA is highly immunogenic and is the major protective antigen in clinically licensed inactivated and live-attenuated influenza vaccines, HA DNA vaccines provide a sensitive study model (15, 16, 18, 30, 3638) to detect the impact of innate immunity on a clinically relevant immunogen.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudotype viruses (psv) were constructed from the following H1N1 influenza strains: A/Brazil/78(BZ78), A/Chile/1/83(CH83), A/Taiwan/1/86(TW86), A/Texas/36/91(TX91), A/Bayern/7/95(BY95), A/Beijing/262/95(BJ95), and A/Solomon Islands/3/06(SI06) (Table 1). The pseudovirus titers were determined by single-round infection of 293A cells [26]. …”
Section: Methodsmentioning
confidence: 99%